A Mix Design Procedure for Alkali-Activated High-Calcium Fly Ash Concrete Cured at Ambient Temperature. (15th April 2018) - Phoo-ngernkham, Tanakorn; Phiangphimai, Chattarika; Damrongwiriyanupap, Nattapong; Hanjitsuwan, Sakonwan; Thumrongvut, Jaksada; Chindaprasirt, Prinya
Abstract : This research focuses on developing a mix design methodology for alkali-activated high-calcium fly ash concrete (AAHFAC). High-calcium fly ash (FA) from the Mae Moh power plant in northern Thailand was used as a starting material. Sodium hydroxide and sodium silicate were used as alkaline activator solutions (AAS). Many parameters, namely, NaOH concentration, alkaline activator solution-to-fly ash (AAS/FA) ratio, and coarse aggregate size, were investigated. The 28-day compressive strength was tested to validate the mix design proposed. The mix design methodology of the proposed AAHFAC mixes was given step by step, and it was modified from ACI standards. Test results showed that the 28-day compressive strength of 15–35 MPa was obtained. After modifying mix design of the AAHFAC mixes by updating the AAS/FA ratio from laboratory experiments, it was found that they met the strength requirement.